Effect of forest fragment size on Polistinae (Hymenoptera, Vespidae) in a transitional area of Cerrado and Atlantic Forest in south central Minas Gerais state, Brazil - Coelho, Maria Luiza Santana; Gouvêa, Taiguara Pereira de; Clemente, Mateus Aparecido; Souza, Marcos Magalhães de (EntomoBrasilis, 2022)
Ecosystem fragmentation negatively affects biological diversity and compromises different environmental services. This situation occurs in two important biomes in Brazil, the Atlantic Forest and the Cerrado. There is little information on the effects of fragmentation on animal taxa, including social wasps. It was hypothesized that fragments that are small in size and subject to anthropogenic pressures have reduced social wasp richness and colony numbers. This study aimed to investigate the effect of forest fragmentation on Polistinae richness and colony number at Atlantic Forest and Cerrado sites in southern central Minas Gerais State, southeastern Brazil. The study was conducted in three fragments, Mata do Baú, Cachoeira da Lajinha, and Cachoeira do Padeiro, from October 2020 to March 2021, using active collection to record social wasp species and colony numbers. A total of 42 species and 80 colonies were recorded in the three fragments. Forest fragment size alone did not influence social wasp communities, but communities were significantly affected by a combination of factors, including fragment size, adjacent vegetation, and anthropogenic pressures. Species richness was higher in Mata do Baú and Cachoeira da Lajinha, which did not differ from each other, than in Cachoeira do Padeiro; however, all fragments had exclusive communities. Therefore, an increase in anthropogenic pressure in any of the three fragments may lead to losses in social wasp species.